Viscoelastic material characterization and novel damper development for sound proof HDD - Yeo, Hui Jie. (2009)
Hard Disk Drive (HDD) is a device that is used to store digitally encoded data on rapidly rotating platters. With the increasing use of HDD in science and technology, HDD must be able to have a fast accessing speed and large storage capacity with a smaller physical size. As a result of the small form factor HDD application in consumer electronics products, the small form factor HDD has to increase its true performance index and its spinning speed. As a result of these improvements, noise generated in HDD will become a problem. Extensive experimental studies have been carried out on the precision reading and writing of the data but limited research is done on the acoustic noise level in HDD. Therefore in an attempt to reduce the acoustic noise level of a 1.8 inch HDD, experimental and numerical study is carried out in this report to develop a novel HDD cover with viscoelastic damper. The report consists of experimental and numerical studies, of which the first part is an experimental study of viscoelastic material of the damper materials for HDD, and the second part is designing and analysis of the HDD cover with the viscoelastic damper. Lastly, the effect of the new cover design on the HDD acoustic noise reduction is evaluated with the HDD vibro-acoustic analysis.